Phase synchronisation in the Kuroshio Current System - Klose, Ann Kristin; van Westen, René M.; Dijkstra, Henk A. (Copernicus Publications, 2020)
The Kuroshio Current System in the North Pacific displays path transitions on a decadal timescale. It is known that both internal variability involving barotropic and baroclinic instabilities and remote Rossby waves induced by North Pacific wind stress anomalies are involved in these path transitions. However, the precise coupling of both processes and its consequences for the dominant decadal transition timescale are still under discussion. Here, we analyse the output of a multi-centennial high-resolution global climate model simulation and study phase synchronisation between Pacific zonal wind stress anomalies and Kuroshio Current System path variability. We apply the Hilbert transform technique to determine the phase and find epochs where such phase synchronisation appears. The physics of this synchronisation are shown to occur through the effect of the vertical motion of isopycnals, as induced by the propagating Rossby waves, on the instabilities of the Kuroshio Current System.
Keywords: Oceanography; Palaeontology; SDG 13 - Climate Action